A Review on the Recent Development of Solar Absorption and Vapour Compression based Hybrid Air Conditioning with Low Temperature Storage - D. N., Noor; Azim, Arshad; Z., Azran; Hassan, Ibrahim; F., Basrawi (EDP Sciences, 2015, 2016)
Conventional air conditioners or vapour compression systems are main contributors to energy consumption in modern buildings. There are common environmental issues emanating from vapour compression system such as greenhouse gas emission and heat wastage. These problems can be reduced by adaptation of solar energy components to vapour compression system. However, intermittence input of daily solar radiation was the main issue of solar energy system. This paper presents the recent studies on hybrid air conditioning system. In addition, the basic vapour compression system and components involved in the solar air conditioning system are discussed. Introduction of low temperature storage can be an interactive solution and improved economically which portray different modes of operating strategies. Yet, very few studies have examined on optimal operating strategies of the hybrid system. Finally, the findings of this review will help suggest optimization of solar absorption and vapour compression based hybrid air conditioning system for future work while considering both economic and environmental factors.